Cerebral venous sinus thrombosis in a young boy after dexamethasone abuse: A rare case report - Suchismita Mishra; Jasmita Satapathy; Deergha Pareek; Yamijala N Srija (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2023)
We report a case of a 21-year-old boy who presented to the emergency department with headache, vomiting, diplopia, incoherent speech, and seizure. On thorough interrogation, the patient gave a history of steroid (dexamethasone) abuse since past three years. On examination, there was limitation of ocular movement and papilledema. Magnetic resonance (MR) venography showed superior sagittal sinus thrombosis extending to the left straight and sigmoid sinuses. Long-term use of dexamethasone can predispose one to cerebral venous sinus thrombosis. Hence, careful history-taking is mandatory in all such cases, especially when laboratory investigations reveal no abnormalities.